2017
DOI: 10.3390/inventions2010005
|View full text |Cite
|
Sign up to set email alerts
|

A Quick Overview of Compact Air-Cooled Heat Sinks Applicable for Electronic Cooling—Recent Progress

Abstract: Abstract:This study provides an overview regarding enhancement of an air-cooled heat sink applicable for electronic cooling subject to cross-flow forced convection. Some novel designs and associated problems in air-cooled heat sinks are discussed, including the drawback of adding surfaces, utilization of porous surfaces such as metal foam or carbon foam, problems and suitable applicable range of highly interrupted surfaces (louver or slit) and longitudinal vortex generator. Though the metal foam may accommodat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Through some tedious mathematical manipulation and simplification, the final partial differential equation of the heat pipe can be derived as shown in equation (1), where BC at x = 0 is T b , BC at x = L is the insulated tip. The detailed derivation is shown in the appendix:…”
Section: Schematics Of the Physical Model And The Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Through some tedious mathematical manipulation and simplification, the final partial differential equation of the heat pipe can be derived as shown in equation (1), where BC at x = 0 is T b , BC at x = L is the insulated tip. The detailed derivation is shown in the appendix:…”
Section: Schematics Of the Physical Model And The Experimental Setupmentioning
confidence: 99%
“…For the last 20 years, electronic cooling solutions for notebooks, PCs and servers have been based primarily on steadystate design criteria [1][2][3]. Under these criteria, aluminum extrusion heat sinks or stacked fins made from copper or aluminum are widely adopted as air-cooling thermal solutions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional heat sink systems, consisting of fins and air-cooling systems, are found to be inadequate, not only due to constraints of physical space but also because of lower thermal properties. 1 Advanced heat dissipation systems deployed include microheat pipes, 2 heat pumps, 3 thermoelectric cooling, 4 boiling heat transfer, 5 and jet impingment. 6 Among these, the liquid-cooled microchannel heat sink (MCHS) is proven effective in cooling microelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The increased power density that needs to be dissipated, which is often greater than 100 W/cm 2 , requires the development of innovative advanced heat sink systems. Conventional heat sink systems, consisting of fins and air‐cooling systems, are found to be inadequate, not only due to constraints of physical space but also because of lower thermal properties 1 . Advanced heat dissipation systems deployed include microheat pipes, 2 heat pumps, 3 thermoelectric cooling, 4 boiling heat transfer, 5 and jet impingment 6 …”
Section: Introductionmentioning
confidence: 99%
“…The result revealed that the V-type fin array gave better heat transfer performance than the vertical fin array and 'V' fin with bottom spacing type array. Various studies related to the heat sink are found in the literature to enhance heat transfer coefficient [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%